The regional distribution of anxiety disorders: implications for the Global Burden of Disease Study, 2010. Issue 4 (22nd July 2014) - Baxter, Amanda J.; Vos, Theo; Scott, Kate M.; Norman, Rosana E.; Flaxman, Abraham D.; Blore, Jed; Whiteford, Harvey A.
Abstract Anxiety disorders are increasingly acknowledged as a global health issue however an accurate picture of prevalence across populations is lacking. Empirical data are incomplete and inconsistent so alternate means of estimating prevalence are required to inform estimates for the new Global Burden of Disease Study 2010. We used a Bayesian meta‐regression approach which included empirical epidemiological data, expert prior information, study covariates and population characteristics. Reported are global and regional point prevalence for anxiety disorders in 2010. Point prevalence of anxiety disorders differed by up to three‐fold across world regions, ranging between 2.1% (1.8–2.5%) in East Asia and 6.1% (5.1–7.4%) in North Africa/Middle East. Anxiety was more common in Latin America; high income regions; and regions with a history of recent conflict. There was considerable uncertainty around estimates, particularly for regions where no data were available. Future research is required to examine whether variations in regional distributions of anxiety disorders are substantive differences or an artefact of cultural or methodological differences. This is a particular imperative where anxiety is consistently reported to be less common, and where it appears to be elevated, but uncertainty prevents the reporting of conclusive estimates. Copyright © 2014 John Wiley & Sons, Ltd.